Distribution Patterns and Abundance of the Dura Andat, Agonoscelis pubescens (Thunb.), and other Pentatomids Across Habitat Patches in the Central Clay Plain of Sudan* - Mohamed, El Sayed El Bashir; Bilal, Alawia F. (University of Khartoum Journal of Agricultural Sciences, 2023)
Field surveys were carried out at three locations in the central clay plain of Sudan at Gedarif, Blue Nile and North Darfur States. The objective was to determine the most preferred resting sites of the dura andat, Agonoscelis pubescens , and other associated pentatomid species. These sites are where the chemical control campaigns of this pest are conducted every year. The results showed that A. pubescens preferred certain types of trees as resting sites and that different pentatomid species aggregated and stayed together with it at these sites. A. pubescens was the main species sheltering on trees, while Carbula pedalis, an unconfirmed pest of sorghum, was the main species sheltering in mountain caves. Each of these two species seemed to join with a set of specific group of pentatomids, which differed from those associated with the other. It is argued that control of C. pedalis may be unnecessary if it is proved that this insect is neither a pest of sorghum nor of any other main crop.